Sclerosing mesenteritis - rare cause of abdominal pain and intra-abdominal mass: a case report - Yadgire, Atul; Tiwari, Saurabh J.; Umale, Narayan P. (International Journal of Research in Medical Sciences, 2017)
Sclerosing mesenteritis is a rare, benign, and chronic fibrosing inflammatory disease with unknown etiology that affects the mesentery of small bowel and colon. The disease has two well-established histological types: the acute or subacute form known as mesenteric panniculitis and the chronic form known as retractile or sclerosing mesenteritis. Because sclerosing mesenteritis lacks special clinical manifestations and typical signs, the patients are very easily misdiagnosed. The correct diagnosis of sclerosing mesenteritis depends on pathological examination after laparotomy. We report a case of sclerosing mesenteritis in a 55-year-old male who presented with chronic abdominal pain and intra-abdominal mass. He was misdiagnosed as lymphoma by Computed Tomography and then underwent exploratory laparotomy. Histopathological examination revealed it to be sclerosing mesenteritis. This patient went well and lives without recrudescence till date.